Design and Development of the Transmission Shaft Electromagnetic Brake and Half Shaft Wet Brake Integrated System in Heavy Vehicle - Ma Hongge (Jixie chuandong)
In order to solve the traditional heavy vehicle braking system braking performance are not stable,installation space limitations,a brake integrated system scheme through arranging electromagnetic brake on the drive axle dynamic input shaft and layout wet brake Inside the integral drive axle is proposed,the mathematical model of integrated brake system is established through the analysis of the layout scheme of device structure and working principle,and through the experimental methods to verify the feasibility of integrated brake system.The results show that the half shaft wet brake torque presents increased trend,at the end of the braking,the brake torque of the brake integrated system is provided solely by the half shaft wet brake,the electromagnetic brake torque first increased and then decreased,the torque at the end of the braking become to zero; the brake integrated system braking torque decreases with the half shaft speed decreases,a certain fluctuation exists during the period; in the braking process of brake integrated system,the wet brake load can be significantly reduced and the oil temperature can be controlled in a suitable range.